Effect of Gradient on Pedestrian Flow Characteristics under Mixed Flow Conditions - Gupta A.; Singh B.; Pundir N. (My University, 2025)
Present study is based on the survey of three locations from Central Business District (CBD) area of Dharamshala. With the help of videographic survey during the peak hours, pedestrian flow characteristics were extracted. Age, sex and baggage conditions of pedestrians were also assessed with the help of captured videos. Relationships between speed-density, flow-density, flow-speed and flow-space were projected through graphs. Based on the collected data, pedestrian flow behavior models were developed and those were compared with the models developed for plain topography regions. Pedestrian Level of Service (LOS) was derived from standards laid down by Indian Road Congress (IRC) codes. © 2017 The Author(s).